Components of Banisteriopsis caapi, a Plant Used in the Preparation of the Psychoactive Ayahuasca, Induce Anti-Inflammatory Effects in Microglial Cells - Beatriz Werneck Lopes Santos; Daniel Carneiro Moreira; Tatiana Karla dos Santos Borges; Eloisa Dutra Caldas (Molecules, 2022)
Banisteriopsis caapi is used to prepare the psychoactive beverage ayahuasca, and both have therapeutic potential for the treatment of many central nervous system (CNS) conditions. This study aimed to isolate new bioactive compounds from B. caapi extract and evaluate their biological activity, and that of the known β-carboline components of the plant (harmine, harmaline, and tetrahydroharmine), in BV-2 microglial cells, the in vivo activation of which is implicated in the physiopathology of CNS disorders. B. caapi extract was fractionated using semipreparative liquid chromatography (HPLC-DAD) and the exact masses ([M + H]+m/z) of the compounds in the 5 isolated fractions were determined by high-resolution LC-MS/MS: F1 (174.0918 and 233.1289), F2 (353.1722), F3 (304.3001), F4 (188.1081), and F5 (205.0785). Harmine (75.5–302 µM) significantly decreased cell viability after 2 h of treatment and increased the number of necrotic cells and production of reactive oxygen species at equal or lower concentrations after 24 h. F4 did not impact viability but was also cytotoxic after 24 h. Most treatments reduced proinflammatory cytokine production (IL-2, IL-6, IL-17, and/or TNF), especially harmaline and F5 at 2.5 µM and higher concentrations, tetrahydroharmine (9.3 µM and higher), and F5 (10.7 µM and higher). The results suggest that the compounds found in B. caapi extract have anti-inflammatory potential that could be explored for the development of treatments for neurodegenerative diseases.